2014
DOI: 10.2118/147395-pa
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Laboratory Testing of Illitic Sandstone Outcrop Cores With HCl-Alternative Fluids

Abstract: Summary Illitic sandstone reservoirs are sensitive to hydrochloric-acid (HCl) -based fluids. When HCl contacts illite, it breaks down and causes fines migration and formation damage. The migration of fines through the porous media will block the pores, reduce permeability, and decrease the production rate of oil and gas wells. A thorough literature review showed that all clay minerals are essentially unstable in HCl at temperatures greater than 300°F. In turn, there is a need to search for stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The iron can be chelated from chlorite mineral, calcium from calcite and dolomite, magnesium can be chelated from dolomite, and aluminum can be chelated from clay minerals such as illite and kaolinite. Both EDTA and HEDTA are compatible with Berea sandstone cores, and no fines were observed in the collected effluent samples (Mahmoud et al 2015;2011). Figure 3 shows the effect of using HEIDA chelating agent on sulfate scale precipitation and on the enhancement of core permeability.…”
Section: Resultsmentioning
confidence: 99%
“…The iron can be chelated from chlorite mineral, calcium from calcite and dolomite, magnesium can be chelated from dolomite, and aluminum can be chelated from clay minerals such as illite and kaolinite. Both EDTA and HEDTA are compatible with Berea sandstone cores, and no fines were observed in the collected effluent samples (Mahmoud et al 2015;2011). Figure 3 shows the effect of using HEIDA chelating agent on sulfate scale precipitation and on the enhancement of core permeability.…”
Section: Resultsmentioning
confidence: 99%
“…A lingering issue surrounding this premise is the degree of effectiveness that a given APCA can have for Ca 2ϩ in the pH range of 0 to 3, which is the pH range where the most acidic proton of an APCA will undergo dissociation and generate a binding (stabilizing) site (the carboxylate ion) . Previous work with GLDA/HF from other researchers has already indicated that CaF 2 precipitation is to be expected (Mahmoud et al 2014) even when using the fluid at a pH of 3.8, which, in principle and in the absence of competing equilibria, should provide improved complexation of Ca 2ϩ . The conclusion reached by Mahmoud et al (2014) is that, to minimize the negative effects associated with free fluoride (F -), the concentration of HF should not exceed 1% when using NaH 3 GLDA.…”
Section: Problem Frameworkmentioning
confidence: 98%
“…Previous work with GLDA/HF from other researchers has already indicated that CaF 2 precipitation is to be expected (Mahmoud et al 2014) even when using the fluid at a pH of 3.8, which, in principle and in the absence of competing equilibria, should provide improved complexation of Ca 2ϩ . The conclusion reached by Mahmoud et al (2014) is that, to minimize the negative effects associated with free fluoride (F -), the concentration of HF should not exceed 1% when using NaH 3 GLDA. Notably, this conclusion appears to emanate from work centered on other APCA, such as EDTA and HEDTA, which are not as soluble as GLDA in pH lower than 3.…”
Section: Problem Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…They were followed by Frenier and co-workers (2001Frenier and co-workers ( , 2003Frenier and co-workers ( , 2004 who introduced HEDTA. Mahmoud et al used GLDA to stimulate carbonate (LePage et al 2011;Mahmoud et al 2011aMahmoud et al , 2011b and sandstone formations (Mahmoud et al 2015) to remove carbonates and oxides minerals. Reyes et al (2013) examined a new chelant.…”
Section: Introductionmentioning
confidence: 99%